2022
DOI: 10.1001/jamaoncol.2021.6826
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Genetic Ancestry With the Molecular Subtypes and Prognosis of Childhood Acute Lymphoblastic Leukemia

Abstract: IMPORTANCERacial and ethnic disparities persist in the incidence and treatment outcomes of childhood acute lymphoblastic leukemia (ALL). However, there is a paucity of data describing the genetic basis of these disparities, especially in association with modern ALL molecular taxonomy and in the context of contemporary treatment regimens.OBJECTIVE To evaluate the association of genetic ancestry with childhood ALL molecular subtypes and outcomes of modern ALL therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 44 publications
8
46
2
Order By: Relevance
“…This finding is consistent with a recent study showing that patients with African, Native American and East Asian genetic ancestry have higher proportion of this genotype as compared to those with European ancestry among whom approximately 3% of the patients have this genotype. 8 Our study yielded a 5-year event-free survival of 84.4% (95% CI, 80.6-88.3) and 5year overall survival of 88.9% (95% CI, 85.5-92.4), results consistent with those of other clinical trials conducted after 2000 (Supplemental Table 4). The recent improvement in outcome was largely due to the use of more refined risk-adapted treatment including measurement of MRD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with a recent study showing that patients with African, Native American and East Asian genetic ancestry have higher proportion of this genotype as compared to those with European ancestry among whom approximately 3% of the patients have this genotype. 8 Our study yielded a 5-year event-free survival of 84.4% (95% CI, 80.6-88.3) and 5year overall survival of 88.9% (95% CI, 85.5-92.4), results consistent with those of other clinical trials conducted after 2000 (Supplemental Table 4). The recent improvement in outcome was largely due to the use of more refined risk-adapted treatment including measurement of MRD.…”
Section: Discussionsupporting
confidence: 89%
“…Contemporary therapies have yielded 5-year event-free survival and overall survival rates exceeding 80% and 90%, respectively, for childhood acute lymphoblastic leukemia (ALL) [1][2][3][4]. TCF3-PBX1, resulting from the t(1;19) (q23;p13), is one of the most frequent genetic abnormalities, affecting 3% to 12% of pediatric B-ALL cases, depending on the genetic ancestry [1,[5][6][7][8]. This genotype had historically been associated with a poor prognosis [9][10][11] and increased central nervous system (CNS) relapse [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been described that when the Amerindian (indigenous) ancestry is higher, the ETV6-RUNX1 is less common. This type of ancestry has been consistently associated with a high incidence and poor prognosis of childhood ALL and in a recent study was reported that the Amerindian is the most prevalent ancestry in pediatric population of MC ( 148 , 149 ). Until date, the reasons behind this relationship has not been established and further investigation is required for explaining the high incidence and mortality rates observed in Hispanic populations ( 150 ).…”
Section: Discussionmentioning
confidence: 95%
“…In the same context, it has been observed that the incidence of ALL subtypes and genetic susceptibility to ALL varies according to geographic regions and ancestry of populations. Recently, it has been reported that in a population with a higher prevalence of Native American ancestry, the ETV6::RUNX1 fusion gene is found with lower frequency, and this population was associated with poor prognosis ( 29 ). This directly correlates with the ancestry analysis that was performed in Mexican ALL patients using AIMs (Ancestry-informative marker, single nucleotide polymorphism of frequency differences between populations) which showed that they belong to the mestizo group, enriched mainly by a Native American ( 30 ).…”
Section: Discussionmentioning
confidence: 99%